1990
DOI: 10.1037/0278-6133.9.3.330
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analytic evaluation of couples weight-loss programs.

Abstract: Applied Hedges and Olkin's (1985) statistical meta-analytic procedures to summary data from all published studies that compared behavioral weight-control programs that formally involved partners in treatment (couples programs) to similar programs in which subjects participated alone (subject-alone programs). Based on tests of effect sizes, couples programs are significantly superior to subject-alone programs at posttreatment (p less than .05). A nearly significant (p = .06) statistical superiority for couples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(127 citation statements)
references
References 28 publications
3
119
2
Order By: Relevance
“…This meant it was not possible to carry out a meta‐analysis. The two areas that previously have had a number of couple‐focused intervention studies conducted, weight loss and HIV prevention, found that couple‐focused interventions were successful in enabling weight loss post‐treatment (Black et al ., 1990), although the effects were not sustained, and reduced unprotected sexual intercourse and increased condom use relative to control groups (Burton et al ., 2010). This evidence for possible effectiveness of couple‐based interventions suggests that, in the health behaviour change areas identified in our review, further studies are needed to assess the effectiveness of couple‐based versus individual interventions, despite increased resources and logistical challenges involved with trying to recruit and retain couples (Coyne & Lepore, 2006; McGrath et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This meant it was not possible to carry out a meta‐analysis. The two areas that previously have had a number of couple‐focused intervention studies conducted, weight loss and HIV prevention, found that couple‐focused interventions were successful in enabling weight loss post‐treatment (Black et al ., 1990), although the effects were not sustained, and reduced unprotected sexual intercourse and increased condom use relative to control groups (Burton et al ., 2010). This evidence for possible effectiveness of couple‐based interventions suggests that, in the health behaviour change areas identified in our review, further studies are needed to assess the effectiveness of couple‐based versus individual interventions, despite increased resources and logistical challenges involved with trying to recruit and retain couples (Coyne & Lepore, 2006; McGrath et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Using the keyword search method, we searched the databases MEDLINE, Embase, Web of Knowledge, and PsycINFO for articles published in the English language between January 1990 (when the review on weight loss interventions (Black et al ., 1990) was carried out, as based on a search of earlier literature, no couple‐focused interventions on other topics were identified prior to this date) and June 2014. To avoid exacerbating publication bias, we decided not to include unpublished data and dissertations (Ferguson & Brannick, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using an author-de®ned criteria for obesity is not unprecedented in meta-analytical research in obesity; 5 and may be better than having no exclusion criteria at all for obesity, as other meta-analyses have done. 4,5,10 Nonetheless, caution is warranted when interpreting comparative differences among program types. It may be that exercise is a more effective intervention strategy for individuals who are more obese 4,5 or older than those included in the narrowly-de®ned population de®ned by this meta-analysis.…”
Section: Descriptive Datamentioning
confidence: 99%
“…Small group interventions have also been shown to be effective in promoting weight loss [8,9] and maintenance, and have the added advantage of being more costeffective [10]. Increasing social support [11][12][13] through small group interaction has proven to be equally or more effective than individual behavioral therapy for obesity [14]. A recent systematic review of studies that randomized obese participants to either a group or individual mode of weight loss treatment delivery concluded that group interventions were not only more effective, but may be more resource saving in terms of total health professional hours required per participant [14].…”
Section: Introductionmentioning
confidence: 99%